Fault-Tolerant Control for Multi-Quadcopter with Suspended Payload under Wind Disturbance - FARRAS, ALIF AL; SANTOSO, ARI; NUGRAHA, YURID EKA (Department of Electrical Engineering ITS and FORTEI, 2024)
Delivering payload with multiple quadcopters necessitates a reliable backup system. This research introduces a fault-tolerant design specifically for multi-drone payload transportation. The system employs formation control, ensuring the weight is evenly distributed among all functioning drones. This research tackles the challenge of reliable payload delivery with multi-drone systems. It proposes a new fault-tolerant control system specifically designed for this purpose. The system addresses a limitation in existing solutions by incorporating a simple PD controller alongside a fault-tolerant strategy. This approach allows the system to maintain operation even if a drone malfunctions. The paper further demonstrates the system's effectiveness through simulations. Results show the system's ability to maintain stability with minimal altitude loss (only 6.3cm) and rapid position reconfiguration (within 3.96 seconds) even under windy conditions. These findings highlight the potential of this fault-tolerant design to significantly improve multi-drone payload delivery, especially for missions requiring high levels of stability and redundancy.